Genres and Trends in Narratives of Conflict in Kenya: Ngugi Wa Thiong’o and Micere Githae Mugo Examined - Saje , Umar (International Journal of Psychosocial Rehabilitation, 2020)
Ngugi Wa Thiong’o’s The Trial of Dedan Kimanthi; (1976) co-authored with Micere Githae Mugo and his novel Petals of Blood (1977) depict the writers’ forte in the area of social realism and these works present a basis for the assessment of the socio-political and cultural conflicts in Kenya from the socialist plane. In these works, the writers’ pre-occupation is significantly with the lucid portrayal of the Kenyan society, taking into cognizance the relationship between the bourgeoisie and the proletariats, on the one hand, and the conflict between the imperialists and the African people, on the other hand, over the occupation and control of the African territory. Significantly, the heroic resistance of the Kenyan people fighting both foreign and local forces of exploitation and domination is examined in order to analyse how this literary thematic concern is reflected in these works. The paper, therefore, discusses the conflict in both texts, which are essentially a play and a novel, two very important literary genres that have proximity to everyday life. In this regard, the dynamics of the armed resistance and the political struggle against the historical and cultural backgrounds of the Kenyan people will be critically examined. This will be done with a view to exploring how the historical, cultural and political conflicts have come to bear on the new cultural and political cartographies of the society under reference, as a result of class struggle and class interest throughout the history of the society being critically examined.